Interaction of p-glycoprotein inhibitor-Verapamil- and Colchicine on some Neurobehavioral and Biochemical parameters in mice - Tayseer Shaker Mahmood; Raghdaa Dawood Obaid; Duraid Abdul-Hadi Abass (Zien Journals, 2022)
Neurobehavioral methods were used to investigate the effect of co-administration p-glycoproteininhibitor –verapamil- on colchicine –p-glycoprotein substrate given alone and in combination at low andhigh therapeutic oral doses given daily for 3 months in (63) albino mice allocated to (7) equal groups
Keywords: AchE activity; Creatinine kinase; neurobehavioral